Ambiguous publicities: Cultivating doubt at the intersection of competing genres of risk evaluation in Catalan Prisons. (July 2019) - Römer, Johanna
Policymakers in Canada and across Europe have largely embraced the creation of post-disciplinary systems of punishment. In the autonomous region of Catalonia, Spain, this meant expanding connections between prisons and communities, expanding the publics a prison serves. At the same time, in part driven by austerity policies, incarceration in Spain and Catalonia has become more punitive and bureaucratic. Actuarial risk assessments introduced in Catalan prisons in 2009 are an example of this type of reform—designed to facilitate the release of low-risk inmates earlier and to control mobility. Drawing on ethnographic research conducted in Catalan prisons from 2012 to 2014, I show how both actuarial and clinical risk evaluation involved therapists' anticipation of future aggressive acts on the part of inmates. Analyzing risk assessment as a practice and as an ideological frame, I argue that the short-term focus of risk assessments reinforced existing forms of interpreting inmates' actions that therapists attempted to hold at bay. Risk as an ideological frame in the context of austerity contributes to a form of publicity that can further isolate inmates rather than facilitating the construction of community inside and outside of a rehabilitative prison.